Big Data e dados pessoais: questões legais emergentes na perspectiva da Ciência da Informação - Conceição, Gislaine Cristina da (Universidade Federal de São Carlos, 2023)
This research aims to analyze the discussions about legal aspects in the use of data in Information Science, in Brazil, in the last 10 years. In this way, it seeks to answer the following guiding question: How much attention has been paid to legal and privacy aspects in the use of personal data in scientific research over the last ten years of Information Science in Brazil? The theoretical frame of reference was established from the concepts: Big Data; Data Lifecycle; Data; Privacy and Brazilian Regulatory Framework. As for methodology, a domain analysis of bibliographic materials related to data and privacy in Information Science in Brazil was carried out, covering the period from January 2012 to December 2022. In this study, the domain analysis focused on approach 5 ) Historical studies, according to the classification of Smiraglia (2015), and in the approach 6) Historical studies of Hjørland (2002). From the analysis of the works presented in the BRAPCI, Scielo, BDTD, ISKO-Brasil and ENANCIB Databases in the form of Oral Communications and Posters, over the course of the last ten years. Of the total number of publications retrieved, we sought to identify those that had the terms privacy; personal data; law of access to information and general law of protection of personal data, in the title, abstract and/or keywords. Of the results obtained from the Databases, 173 articles were in accordance with the criteria established to be part of the research analysis. The works were categorized and the generation of graphs occurred with information on the temporal distribution of authors and their institutional affiliations; study application area according to the Data Lifecycle in CI; Then, a historical trend analysis of the discussions handled by the ten most collaborative authors with the CVD-CI in the last ten years was performed. The analysis carried out revealed that approximately 75% of the work on the Databases is concentrated in the Life Cycle Data Collection (CVD-CI) stage. There is a lack of studies on the themes of the stages of the data life cycle such as storage, retrieval and disposal of personal data. These themes are fundamental to understand the legal aspects involved in the use of personal data and to guide possible actions in the field of Information Science. It is believed that this research is an important starting point for future research, as it highlights the need for a critical and reflective analysis of aspects involving the use of data and information. This approach is essential to support strategic actions in various sectors of society today.
Big Data and personal data: emerging legal question from Information Science perspective
Keywords: Big Data e dados pessoais; Ciclo de vida de dados; Lei Geral de Proteção de Dados (LGPD); Privacidade; Ciência da Informação; Big Data and personal data; Data lifecycle; General Data Protection Law (LGPD); Privacy; Information science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO